Nicholas Trevet and the Chronology of the Crucifixion - Nothaft, C. Philipp E. (The Mediaeval Journal, 2012)
Abstract The article offers the first edition, translation, and discussion of a quodlibetal quaestio on the date of Christ’s Passion, held in c. 1303 by the Dominican theologian Nicholas Trevet at the University of Oxford. It will be shown that Trevet followed the eleventh-century chronicler Marianus Scottus in arguing that the Dionysiac era placed the birth of Jesus 22 years too late, while at the same time denying that a reform of Christian chronology was necessary. Besides discussing the context and significance of his arguments, the article will also look at the place of this quaestio within Trevet’s own oeuvre.